Kedudukan Material Transfer Agreement sebagai Instrumen Perlindungan Hukum dalam Menjamin Pengalihan Material Kesehatan - Eka Sakti Panca Indraningsih; Hedwig Adianto Mau; Mardi Candra (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The use of materials in health research requires a binding instrument to regulate the distribution of benefits. Material Transfer Agreement (MTA) is an essential material transfer agreement, allowing the management of the transfer through negotiation until a mutually beneficial agreement is reached. In addition, MTA functions as a contract that protects the rights of the parties involved and ensures compliance with regulations, based on the theory of legal protection and authority. This study uses a normative legal method with a statutory and conceptual approach. The collection of legal materials is carried out through the identification of positive legal rules, as well as examining primary, secondary, and tertiary sources. The data is then analyzed from the identification of legal facts to drawing conclusions. The results of the study show that MTA regulations in Indonesia are comprehensively regulated by various levels, including Law Number 17 of 2023 concerning Health (Article 340 paragraph 3), Law Number 11 of 2019 (Article 76 letter h and Article 77 paragraph 1), Government Regulation Number 28 of 2024 (Articles 972, 1025–1031), and Regulation of the Minister of Health Number 85 of 2020 (Articles 4, 5, 6, 7, 9, 14, 15, and 16 paragraph 1). These national legal frameworks complement each other to ensure procedural certainty, biosafety, benefit sharing, protection of intellectual property rights, and sanctions for violators in the transfer of health materials. Although its implementation faces preventive and repressive challenges, MTA has proven essential in bridging national and commercial interests, increasing the capacity of science and technology, and protecting the sovereignty of Indonesia’s genetic resources.